COMPARATIVE ANALYSIS OF ARRUDA-BOYCE (8- CHAIN), GENT, AND ISIHARA HYPERELASTIC CONSTITUTIVE MODELLING ON PT CIPTA DAYA MANDIRIINSANI INDONESIAÃâÃâS INDUSTRIAL RUBBER AND JoRGEN BERGSTRoMÃâÃâS LITERATURE - YUNUS ACHMAD (NIM : 13105051); Pembimbing 1 : Dr. Ir. Bagus Budiwantoro; Pembimbing 2 : Dr. An, ADLI
Indonesia’s great potential as one of the largest rubber producing country in the world isn’t fully utilized. Needed to do more in-depth research about rubber in Indonesia because of its many functional aspects of the rubber on the industry. This research is the further step of previous research on stress strain testing for the PT Cipta Daya Mandiriinsani Indonesia’s rubber industry with NR, NR +, and NBR types at three different strain rates, i.e. 2 mm / min, 19.8 mm / min, and 198 mm / min, as well as rubber material (NR) from the Jorgen Bergström’s literature. This study aims to find the most appropriate model to describe the stress strain behavior of those rubber materials using three constitutive hiperelastic physically-based models which are Arruda-Boyce (8-chain), Gent, and Isihara. Based on test data, the coefficients for each model then can be calculated and used to describe the condition of stress strain relationship for each type of rubber. Comparasion for the goodness of fit of the models is performed with the error method. Where for the case of PT Cipta Daya Mandiriinsani Indonesia’s rubber, Isihara model is the best model to describe the stress strain characteristics. And for the case of Jorgen Bergström’s literature, Isihara model is also the best model to describe the stress strain characteristics.